A Comprehensive Transcriptomic and Proteomics Analysis of Candidate Secretory Proteins in Rose Grain Aphid, Metopolophium dirhodum (Walker) - Atsbha Gebreslasie Gebrekidan; Yong Zhang; Julian Chen (Current Issues in Molecular Biology)
The Rose grain aphid, a notable agricultural pest, releases saliva while feeding. Yet, there is a need for a comprehensive understanding of the specific identity and role of secretory proteins released during probing and feeding. Therefore, a combined transcriptomic and proteomic approach was employed in this study to identify putative secretory proteins. The transcriptomic sequencing result led to the assembly of 18,030 unigenes out of 31,344 transcripts. Among these, 705 potential secretory proteins were predicted and functionally annotated against publicly accessible protein databases. Notably, a substantial proportion of secretory genes (71.5%, 69.08%, and 60.85%) were predicted to encode known proteins in Nr, Pfam, and Swiss-Prot databases, respectively. Conversely, 27.37% and 0.99% of gene transcripts were predicted to encode known proteins with unspecified functions in the Nr and Swiss-Prot databases, respectively. Meanwhile, the proteomic analysis result identified, 15 salivary proteins. Interestingly, most salivary proteins (i.e., 60% of the proteins) showed close similarity to A. craccivora, while 46.67% showed close similarity to A. glycines, M. sacchari and S. flava. However, to verify the expression of these secretory genes and characterize the biological function of salivary proteins further investigation should be geared towards gene expression and functional analysis.